Multiscale analysis of freeze–thaw effects induced by ground heat exchangers on permeability of silty clays. Issue 2 (4th April 2018) - Dalla Santa, G.; Cola, S.; Secco, M.; Tateo, F.; Sassi, R.; Galgaro, A.
Abstract : The freeze–thaw cycles artificially induced in the ground by ground source heat pump systems working at sub-zero temperatures, or during underwater soil excavation, could cause unwanted permanent effects on the hydro-mechanical behaviour of the surrounding deposits. Cohesive deposits present a specific sensitivity to these processes connected to phase changes occurring in the interstitial fluid. The experiments conducted on normally consolidated cohesive soils point out that freeze–thaw cycles can cause a hysteretic increase in vertical permeability of about one order of magnitude, despite a significant concurrent reduction in void ratio. Although the induced freeze–thaw processes are quite constrained close to the borehole heat exchanger, the vertical permeability increase may lead to the risk of connecting aquifers previously separated by cohesive layers, with an overall effect that increases according to the number of probes in the array. Permeability variation appears to be due to the irreversible alteration of the microstructure provoked during the development of freeze–thaw processes. In this paper, the changes of the macroscale hydraulic conductivity are related to changes in the porous microstructural variations, detected in a wide dimensional range by means of a combination of X-ray computed micro tomography, scanning electron microscopy and mercury intrusion porosimetry.